2001
DOI: 10.1073/pnas.041452598
|View full text |Cite
|
Sign up to set email alerts
|

Destabilization of Ca2+-free gelsolin may not be responsible for proteolysis in Familial Amyloidosis of Finnish Type

Abstract: Mutations at position 187 in secreted gelsolin enable aberrant proteolysis at the 172-173 and 243-244 amide bonds, affording the 71-residue amyloidogenic peptide deposited in Familial Amyloidosis of Finnish Type (FAF). Thermodynamic comparisons of two different domain 2 constructs were carried out to study possible effects of the mutations on proteolytic susceptibility. In the construct we consider to be most representative of domain 2 in the context of the full-length protein (134 -266), the D187N FAF variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 42 publications
(48 reference statements)
1
28
0
Order By: Relevance
“…Pathogenic mutations at metal coordinating residues have also been reported for the calciumbinding protein gelsolin, which causes familial amyloidosisFinnish type (6,26). These mutations are located at Ca 2ϩ coordinating residues and, similar to MBR ALS mutations in SOD1, do not destabilize the apoprotein but disrupt metal binding, leading to the generation of amyloidogenic peptides via aberrant proteolysis.…”
Section: Wtl Mutantsmentioning
confidence: 99%
“…Pathogenic mutations at metal coordinating residues have also been reported for the calciumbinding protein gelsolin, which causes familial amyloidosisFinnish type (6,26). These mutations are located at Ca 2ϩ coordinating residues and, similar to MBR ALS mutations in SOD1, do not destabilize the apoprotein but disrupt metal binding, leading to the generation of amyloidogenic peptides via aberrant proteolysis.…”
Section: Wtl Mutantsmentioning
confidence: 99%
“…This mutation eliminates one of the four calcium binding ligands in the second domain of plasma gelsolin, substantially compromising calcium binding. This allows domain 2 of mutant plasma gelsolin to sample unfolded conformations, during which it can be aberrantly proteolytically processed, first in the Golgi and later outside the cell, to form 8 and 5 kDa amyloidogenic fragments that deposit systemically (Figure 1) (Chen et al, 2001, Huff et al, 2003b, Page et al, 2004, Ratnaswamy et al, 2001, Page et al, 2005, Huff et al, 2003a). One copy of the mutant allele appears to result in complete penetrance of FAF.…”
Section: History and Epidemiology Of Gelsolin Amyloidosismentioning
confidence: 99%
“…These partially folded states have aggregation-prone sequences that are exposed and have a high propensity to aggregate because of the high β-sheet propensity of the exposed residues, their hydrophobicity and/or their lack of charge (Chiti et al, 2003, Fernandez-Escamilla et al, 2004). In addition, point mutations can also destabilize normally folded proteins leading to a higher concentration of partially denatured protease-sensitive states, affording a higher concentration of an amyloidogenic protein fragment, as in the case of gelsolin amyloidosis—the subject of this review (Chen et al, 2001, Page et al, 2005, Kangas et al, 2002, Huff et al, 2003a, Huff et al, 2003b, Page et al, 2004, Ratnaswamy et al, 2001). Finally, point mutations in either a precursor protein endoprotease substrate or in the endoprotease itself that processes an intrinsically disordered protein can afford a higher concentration of an amyloidogenic fragment or generate alternative polypeptide fragments with increased amyloidogenic potential, as in the case of Alzheimer’s disease where mutations in APP or γ-secretase lead to more aggregation-prone Aβ 1–42 relative to Aβ 1–40 (Tanzi and Bertram, 2005, Selkoe, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…14,18 The Quickchange method (Stratagene) was used to introduce the E209Q mutation into these constructs and to introduce the R172A mutation into full-length D187N and E209Q.…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…thermodynamic stabilities between the wild-type and FAF-variant proteins. 18 Zapun et al established that wild-type gelsolin domain 2 contains a Ca 2þ binding site and suggested that, if D187 contributes to Ca 2þ binding, the FAF mutations could eliminate a potential source of stabilization. 19 Subsequent studies demonstrated that D187 is a ligand for Ca 2þ binding; wild-type domain 2 binds Ca 2þ with a K d of 650 nM, whereas binding is undetectable at micromolar concentrations for D187N and D187Y domain 2.…”
Section: Introductionmentioning
confidence: 99%